The Effect of Intrinsic Motivation and Transformational Leadership on Employee Performance - Rosbiyati, Rosbiyati; Alam, Iskandar Ali (LPPM STIE KRAKATAU, 2025)
This study examined the effects of employee motivation and transformational leadership on employee performance at the Agriculture Office of Mesuji Regency, Indonesia. It addressed the challenges in human resource management that affect institutional targets and the implementation of agricultural development programs. This study employed a quantitative design using a structured survey of 50 purposively selected employees at the Agriculture Office and applied multiple linear regression to examine the relationships between motivation, transformational leadership, and employee performance. The findings showed that both motivation and transformational leadership positively affected employee performance, with motivation having a stronger impact. Improving employee motivation and transformational leadership are essential to enhance performance at the Mesuji Agriculture Office, supporting effective human resource management, successful agricultural programs, and regional economic growth. The cross-sectional design of this study limits the ability to observe changes over time. Additionally, the focus on a single regional institution may restrict generalizability. The reliance on self-reported data may also introduce perceptual bias. This study provided empirical evidence from a regional government context, highlighting how motivation and transformational leadership influenced employee performance and offering practical recommendations for improving pension services.